#### Answer

$2\sqrt 6$

#### Work Step by Step

$a = 2, b=4, c=-1$
$\sqrt {b^2-4ac}$
=$ \sqrt {4^2 - (4\times2\times-1)}$
=$\sqrt {16-(-8)}$
=$\sqrt {16+8}$
=$\sqrt 24$
=$\sqrt {4\times6}$
=$\sqrt{ 2^2\times6}$
=$2\sqrt 6$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$2\sqrt 6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.